Review artikel: Potensi daun sirih hijau (piper betle l.) dan daun sirih merah (piper crocatum) sebagai antioksidan - Kopong, Maria Vianey Uma; Ni Kadek Warditiani (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Green Betel (Piper betle.) and Red Betel (Piper crocatum) plants belong to the genus Piper from the Piperaceae family. It is known that the leaves of the betel plant have some bioactivity and are used in traditional medicine systems. Many research studies on the betel plant have reported that it contains important chemical components which have pharmacological effects, one of which is as an antioxidant. In this review, we discuss extracts from green and red betel plants as antioxidants and the phytochemical content contained therein. The review that has been made states that the green and red betel leaf extracts have antioxidant activity with a widely used method, namely DPPH (2,2-diphenyl-1-picrylhydrazy) with the results of antioxidant activity tests from the latest journal showing that the n-hexane fraction is more active as an antioxidant. Antioxidant (IC50 26.73 mg/L) compared to the diethyl ether fraction (IC50 114.54 mg/L). The phytochemical content of green and red betel leaf extract is positive for various secondary metabolites such as flavonoids, saponins, terpenoids, steroids, tannins, alkaloids, and phenolic compounds.